GLUCOCORTICOIDS AS IMMUNOSTIMULATORS IN PATHOGENETIC THERAPY OF TUBERCULOSIS - Yareshko, A.G.; Kulish, M.V. (World of Medicine and Biology, 2020)
The immunostimulating effect of corticosteroids in the complex treatment of tuberculosis patients when they are administered in a double physiological dose, every other day, taking into account the circadian rhythm of the function of the hypothalamic-pituitary-adrenal axis was substantiated in the article. Whereas with daily administration, corticosteroids have shown an immunosuppressive effect. Peripheral blood B-lymphocytes are not sensitive to glucocorticosteroid drugs.
Keywords: tuberculosis; pathogenetic therapy; glucocorticosteroids